The intensification of structural repression in Cuba in the wake of the July 2021 protests - Ortiz Hernández, Eimys (REVISTA ELECTRONICA IBEROAMERICANA, 2023)
On July 11, 2021, for the first time since the Triumph of the Revolution, Cuban citizens went on streets shouting “Homeland and life” or “We are hungry.” Despite the harsh repression, the international community opted for a pragmatic approach far from the pretensions of Cuban activism. Thus, this paper analyses the legal response of the authorities aimed at underpinning the systematic violations of human rights and fundamental freedoms. It also examines the reaction of Washington and Brussels, which share a common core: the guarantee of their interests, whether due to the migration issue or the presence of companies in the country.